ANALYSIS OF DECISIONS TO PURCHASE VIRTUAL PRIVATE SERVER PRODUCT IN BALIKPAPAN - Gozali, Lutfi Ahmad; Suharno, Suharno; Achmad, Gusti Noorlitaria (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The use of virtual private server technology is currently growing rapidly in companies to support companies developing applications that are implemented in the company. Lintasarta is a company that provides virtual private server products in Balikpapan which have 24-hour support and a team of internationally certified experts. Researchers are interested in analyzing the antecedents of purchasing decisions of virtual private server products in Balikpapan. The method used in this research is explanation by explaining the variables and objects examined through the collected data. Price, product quality, and technology acceptance models are the main focus discussed. This study took a sample of 30 companies in Balikpapan that use virtual private server products. The analysis technique used is Structural Equation Modeling (SEM) with partial Least Square (PLS) approach. The results showed that the price had a negative and not significant effect on purchase intentions. Product quality has a negative and not significant effect on purchase intention. Technology acceptance models have a positive and significant effect on purchase intentions. Price has a positive and not significant effect on purchasing decisions. Technology acceptance model has a negative and not significant effect on buying decisions. Intention to buy a positive and significant effect on product purchasing decisions. Keywords: Price, Product Quality, Technology Acceptance Model, Purchase Intentions and Purchasing Decisions